Armor-like passivated CsPbBr3 quantum dots: boosted stability with hand-in-hand ligands and enhanced performance of nuclear batteries. Issue 13 (22nd March 2021) - Yang, Dandan; Xu, Zhiheng; Gong, Chunhui; Su, Lin; Li, Xiaoming; Tang, Xiaobin; Geng, Dongling; Meng, Cuifang; Xu, Feng; Zeng, Haibo
Abstract : An armor-like passivation strategy is developed to improve luminous efficiency, storage stability, water resistance and irradiation stability of PQDs. Moreover, PQDs as the transducer component are used in radioluminescent nuclear battery. Abstract : One of the main reasons for the stability issue of inorganic perovskite quantum dots (PQDs) is the fragile protection of surface ligands. Here, an armor-like passivation strategy is proposed to improve the comprehensive stability of PQDs via a solvothermal fabrication method. That is, forming an armor-like protection layer for every single surface point by introducing coupling ligands with strong affinity (both L and X type ligands). The interactions between ligands via hydrogen bonds and strong affinity of ligands to surface atoms are evidenced by 1 H-nuclear magnetic resonance measurements and Fourier transform infrared spectroscopy. As a result, long-term storage stability, high quantum yield, good water resistance, and good radiation hardness of PQDs are achieved. More than 60% of the radioluminescence intensity of the PQD film could be retained under continuous irradiation of 42 kGy. The output power can even be increased by 34.48% compared with the battery without PQD film. This armor-like passivation strategy also provides good reference for the stability improvement of both light-emitting and photovoltaic devices.